Penerapan Metode Activity Based Costing dalam Penentuan Tarif Kamar Hotel pada Mona Plaza Hotel Pekanbaru (Jurnal Kendali Akuntansi, 2024)
Determination of hotel rates is a very important decision. so the hotel needs the right accounting system, especially in calculating costs so that it can determine the appropriate tariff. Activity Based Costing method is one of the accurate methods in determining hotel room rates. The purpose of this study is to apply the Activity Based Costing method in determining hotel room rates and then compare it with the determination of hotel room rates through the cost of goods issued by the hotel. This research uses quantitative descriptive method.  The results showed that the room rates determined through Activity Based Costing resulted in room rates that overstate compared to the rates set by the hotel. Activity Based Costing is not suitable if applied to Mona Plaza Hotel.